Problem of Proving The Existence of God: A Review and Comments on The Proof of Thomas Aquinas - Damianus, Kristianus; Kwirinus, Dismas; Kurniawan, Trio; Marianto, Johanes Robini; Tjipto, Hanafi (Universitas Sanata Dharma, 2025)
This study focuses on the problem of proving the existence of God, offering a review and analysis of Thomas Aquinas' arguments. Aquinas' arguments are presented within the broader framework of theological knowledge, characterized by a highly systematic and detailed approach to proof. Additionally, this paper discusses the perspectives of several scholars who have examined and interpreted Aquinas' arguments on the existence of God. While some of their perspectives share similarities with Aquinas' reasoning, they also introduce differing elements based on their respective viewpoints.This research employs a library-based methodology using hermeneutic phenomenology, which involves collecting, analyzing, organizing, and interpreting relevant literature as well as reflections on faith in God. The primary sources of this study include Thomas Aquinas' Summa Theologiae, while secondary sources provide further context and analysis. The findings of this study indicate that the concept of analogy in Aquinas' argument serves to illustrate a new mode of action that transcends the hierarchical levels of created beings. Aquinas begins his reasoning from a horizontal perspective and subsequently shifts it to a vertical dimension, unveiling a spiritual aspect that revitalizes both life and faith in God.farminggroup.orgmaterassomemory.orgvisualresearchnetwork.orgbrazoriafumc.orgatmamayor.comviralblasts.combloomboomdelivery.com